FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN - JUNITANIA JUNITANIA; SUGIARTO PRAJITNO (Jurnal Bisnis dan Akuntansi, 2019)
The purpose of this study is to test what factors like managerial ownership, institutional ownership, capital structure, profitability, company growth, firm size, audit committee, size of the commissioner’s board, and proportion of independent commissioner’s board affect firm value in non financial firms listed on Indonesia Stock Exchange. Population of this study is non financial firms listed on Indonesia Stock Exchange since 2013 until 2016. This study uses 328 sample data selected by using purposive sampling method. The hypotheses in this research are tested using multiple regression method. the result of this study shows that institutional ownership, profitability, size of the commissioner’s board, and proportion of independent commissioner’s board affect firm value. On the other side, other independent variables, managerial ownership, capital structure, company growth, firm size, and audit committee do not affect firm value.